2003
DOI: 10.1093/jn/133.10.3175
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q Intake Elevates the Mitochondrial and Tissue Levels of Coenzyme Q and α-Tocopherol in Young Mice

Abstract: The main objective of this study was to resolve the issue of whether the amounts of Coenzyme Q (CoQ), which is endogenously synthesized in cells, can be elevated in tissues and mitochondria of young mice by dietary supplementation with CoQ10. The prevalent view is that the uptake of exogenous CoQ by tissues other than plasma and liver either does not occur or is quite minimal. Mice, 6 mo of age, were fed 0, 148 or 654 mg CoQ10/(kg body x d) in their diets for 11 wk. CoQ10 intake enhanced both CoQ9 and CoQ10 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 22 publications
3
57
1
3
Order By: Relevance
“…Several studies seem to confirm the sparing/regenerative effect of CoQ on α-tocopherol in vivo (reviewed in Sohal, 2004). In young adult mice, CoQ 10 intake effectively augmented the α-tocopherol concentration in tissue homogenates and mitochondria from liver, heart, and skeletal muscle (Kamzalov et al, 2003). A similar effect was observed in homogenates and mitochondria of rats (Fig.…”
Section: Antioxidant Roles Of Coq and α-Tocopherol In Inner Mitochondmentioning
confidence: 64%
See 4 more Smart Citations
“…Several studies seem to confirm the sparing/regenerative effect of CoQ on α-tocopherol in vivo (reviewed in Sohal, 2004). In young adult mice, CoQ 10 intake effectively augmented the α-tocopherol concentration in tissue homogenates and mitochondria from liver, heart, and skeletal muscle (Kamzalov et al, 2003). A similar effect was observed in homogenates and mitochondria of rats (Fig.…”
Section: Antioxidant Roles Of Coq and α-Tocopherol In Inner Mitochondmentioning
confidence: 64%
“…It was first shown by Matthews et al (1998) that CoQ 10 intake by 12-or 24-month-old rats increased CoQ content in brain mitochondria and had a neuroprotective effect against 3-nitropropionic acid. Subsequently, a series of studies conducted by us (Lass et al, 1999a,b;Lass and Sohal, 2000;Kwong et al, 2002;Kamzalov et al, 2003;Rebrin et al, 2004) demonstrated that CoQ 10 administration via food to young adult mice or rats caused an increase in amounts of both CoQ 9 and CoQ 10 homologues in plasma, and in homogenates and mitochondria of liver, heart and skeletal muscle (Fig. 6).…”
Section: Effect Of Coq Administration On Endogenous Coq Contentmentioning
confidence: 98%
See 3 more Smart Citations